Sliding wear characterisation of D-gun sprayed alumina-based ceramic composite coatings. (1st January 2014) - Rajakumar, Sundaram; Vijayaraghavan, L.; Mayuram, M.M.; Krishnamurthy, R.
Design of tribo-contact pair is largely centred on efficiency with consideration for minimal wear rate. Wear resistant ceramic/ceramic-composite coatings are widely employed to conserve material in numerous wear combating situations. Thermal sprayed ceramic coatings are widely used in a number of critical applications wherein the present scenario looks for better coatings. The ceramic composite coatings of alumina-matrix were developed through detonation flame spraying and tested for their sliding wear behaviour at different temperatures mating against hardened steel and alumina ceramic coated surface. The results show that among the ceramic depositions alumina-zirconia ceramic composite exhibits least sliding wear especially under higher temperature environment.